INFORMATION ARCHITECTURE CONCEPT MARITIME TRANSPORT LOGISTICS INFORMATION - Sharko, Oleksandr; Movchan, Petro (Science-based technologies, 2025)
At the present stage of development of maritime transport logistics, when organizing international maritime transportation, in addition to ship owners and shippers, banks, brokers, ship operators, charterers, maritime lawyers and other specialists involved in the transportation process become participants in a single process. In these conditions, the development of the concept of information architecture of maritime transport logistics becomes relevant. An overview of the world market of maritime transport transportation is presented. The need to develop means of information support for transportation in the conditions of uncertainty of the influence of the external environment is shown. A methodology for organizing and placing content inside a digital product of the information architecture of transport logistics in conditions of uncertainty is presented. It is shown that the specifics of building information architecture require constant replenishment of input information and its various manifestations hidden behind a large amount of poorly structured information. A gradation and description of the forms of innovative architecture are presented, including an organization system, a tagging system, a navigation system, and a search system. It is established that technologically, the creation of information architecture begins with establishing the reasons for the creation and the circle of consumers of a web resource. Next comes the stage of developing a prototype of the future architecture, a content scheme, links between elements and transformation into visual layouts with a background, banners, text. The organizational principles of constructing the content of the information architecture of maritime transport logistics under conditions of uncertainty of input information are presented. Information architecture helps to take into account the user interests of consumers and serves as a means of facilitating the search for necessary information in the entire labyrinth of available information.